Understanding HIGMill operation at copper regrind application; operating parameters, wear and mineral liberation. (January 2023) - Altun, Okay; Darılmaz, Özgün; Karahan, Erdem; Sert, Tolga; Altun, Deniz; Toprak, Alper; Hür, Anıl
Graphical abstract: Highlights: Detailed investigations were undertaken on industrial scale HIGMill operation at copper regrind circuit. Operational parameters of HIGMill were optimized in terms of energy efficiency. The variation of power draw with operating conditions were investigated. The impacts of solid percent, throughput, size reduction, bead filling, agitator alignment parameters were investigated. The wear of the beads and agitators were also discussed by considering the material they were produced. The influences of HIGMill on liberation of the minerals were also discussed. Abstract: Stirred milling technology has proven its worth globally. The number of installations utilizing this technology has been increasing owing to its energy-efficient operation in fine sizes that leads to improved liberation hence beneficiation performance. HIGMill technology is one of the recent machines having vertical orientation and is in use for wet fine grinding applications. Since the technology is new, understanding its operation regarding to the comminution performance and product specification is of importance for both the academia and industry. This study argues HIGMill operation at copper regrind circuit. Firstly, an initial survey including the concentrate circuit was performed to evaluate the accuracy of the sensors and to provide general knowledge. Then, a series of industrial trials were completed to investigate the influences of operational parameters on energy efficiency, i.e., solid content, the type of grinding media, the alignment of the agitators, agitator material, and bead filling. In the final stage of the study, liberation characteristics of HIGMill products were assessed to provide knowledge on their contribution to the liberation performance of the minerals.